Serological, fragmentomic, and epigenetic characteristics of cell-free DNA in patients with lupus nephritis - Wang, Fang; Miao, Hai-bing; Pei, Zhi-hua; Chen, Zhen (Frontiers in Immunology, 2022)
Objectives: The biological characteristics of plasma circulating cell-free DNA (cfDNA) are related to the pathogenesis of lupus nephritis (LN). The aim of this study was to explore the biological characteristics of cfDNA in patients with LN in terms of serology, fragment omics, and epigenetics, and to discuss the possibility of liquid biopsy for cfDNA as an alternative to conventional tissue biopsy. Methods: cfDNA was extracted from plasma samples of 127 patients with systemic lupus erythematosus (64 with LN, 63 without LN). The cfDNA concentration was determined using the Qubit method. Next-generation sequencing cfDNA methylation profiling was performed for three LN patients and six non-LN patients. The methylation panel was designed based on data from The Cancer Genome Atlas cohort. The fragmentation index, motif score, and DELFI score were calculated to explore the fragmentation profile of cfDNA in patients with LN. Statistical and machine learning methods were used to select features to calculate the methylation scores of the samples. Results: Patients with LN had significantly lower cfDNA concentrations (P = 0.0347)than those without LN. This may be associated with the presence of anti-double-stranded DNA antibodies (r = –0.4189; P = 0.0296). The mean DELFI score (proportion of short fragments of cfDNA) in patients with LN was significantly higher than that in patients without LN (P = 0.0238). Based on the pan-cancer data, 73, 66, 8, and 10 features were selected and used to calculate the methylation scores. The mean methylation scores of these features in patients with LN differed significantly from those in patients without LN (P = 0.0238). Conclusions: The specificity of cfDNA in patients with LN was identified using serological, fragmentomic, and epigenetic analyses. The findings may have implications for the development of new molecular markers of LN.